OMICS technologies and personalized vaccination in the COVID-19 era - Vassilios Fanos; Melania Puddu; Michele Mussap (Hygeia Press di Corridori Marinella, 2022)
The effectiveness of SARS-CoV-2 vaccines is currently undermined by the rapid spread of variants of concern affecting an increasing number of people worldwide. Thus, new vaccine candidates are required to limit new waves of infections. On the one hand, the development of personalized vaccines, both on a personal and population level, may overcome the inter-individual heterogeneity in vaccine-induced immune responses and in adverse side effects. On the other hand, the development of a universal coronaviruses vaccine broadly protective against all betacoronaviruses may overcome the coronaviruses genetic polymorphism due to the generation of new genomes and homologous genetic recombination in multiple species. The preparation of a tailored and universal vaccine, that is an "ideal" vaccine, could be realized with the contribution of the system biology approach and, in particular, of metabolomics, in conjunction with a global policy strategy and adequate public governance.